COMPARISON OF FAILURE CRITERIA FOR WOOD IN TENSILE-SHEAR STRESS STATE - Eliška Šmídová; Petr Kabele (Acta Polytechnica CTU Proceedings, 2017)
An orthotropic failure criterion enhancing the Lourenco's criterion by a shear strength multiplier and a maximum shear strength upper bound has been recently proposed and validated for timber under tensile and shear loading by the authors. The paper discusses its applicability for predicting strength in comparison with Tsai-Hill criterion, Hankinson's and Hyperbolic formula applying the two above mentioned enhancements of the Lourenco's criterion. Experimental data available in the literature for off-axis tensile and shear test of Sitka spruce (Picea sitchensis Carr.), Katsura (Cercidiphyllurn japonicurn Sieb. and Zucc.), Douglas fir (Pseudotsuga menziesii), Douglas fir laminated veneer and Cupiúba (Goupia glabra) are used for the purpose of this study.